The Rediscovery of a Labour Camp on the Construction Site of the Stalin Monument in Prague - Hasil, Jan; Kyselý, René; Pilař, Daniel (Acta Universitatis Lodziensis. Folia Archaeologica, 2022)
The rediscovery of a labour camp on the construction site of the Stalin Monument in Prague in spring 2021 was the result of a construction project of the Municipality of Prague. Until then, the existence of this specific site had not been reflected neither in the historical memory of the place nor in the literature devoted to the monstrous monument (dismantled in 1962), which was both a superb work of art and engineering and the most significant material manifestation of the cult of Stalin’s personality outside the USSR. The discovered remains of the camp’s modest, purely purpose-built buildings, as well as the artifacts and ecofacts that illustrate the living conditions of its inhabitants, contrast sharply with the costly, expressive, and landscape-dominating monument. The results of the archaeological research make a distinctive contribution to the contemporary debate on the nature of the Stalinist regime in Czechoslovakia, as they thematise the bloodless yet pervasive aspect of the regime’s repressiveness.